Formation of Morality of Students of Pedagogical Higher Education Institutions Specialized in “Physical Training”: Problems and Ways of Their Solution - Feuyerman, Vasyl (Pedagogical Discourse, 2012)
The most vital problem of modern pedagogy is studied in the article. It is a formation of teenager’s morality, a special attention in this process is paid to the students of physical training department.